Relationship of Opening CSF Pressure and Visual Field Defect in Idiopathic Intracranial Hypertension - Paybast, Sepideh; Assarzadegan, Farhad; Safarpoor Lima, Behnam; Koosha, Mohsen (International Clinical Neuroscience Journal, 2018)
Background: Idiopathic intracranial hypertension (IIH) is an increased intracranial pressure with normal cerebrospinal fluid (CSF) characteristic in the absence of identifiable causes. The most important complication of this disorder is visual impairment. So far, no comprehensive study has been done on the relationship between the opening CSF pressure and visual field defect in IIH. Methods: In this study, 35 patients with increased intracranial pressure who fulfilled modified Dandy’s criteria underwent ophthalmologic examination and lumbar puncture. The opening CSF pressure was categorized into mild (25-30), moderate (30-40) and severe (>40). The degree of visual field defect was reported both quantitatively and qualitatively. Eventually, the statistical relationship was established among these variables. Results: The mean opening CSF pressure was 33.71 CmH2o. Twelve patients had minor CSF pressure, whereas in 14 and 9 patients the CSF pressure was respectively moderate and severe. There was not statistically significant relationship between the visual field defect and CSF pressure. The most common patterns of visual field involvement were enlarged blind spot and peripheral restriction. Conclusion: The most important morbidity in IIH is visual impairment. According to the findings, the visual field impairment is not pertinent to CSF pressure. In other words, neither high CSF pressure predicts intense visual defect, nor low CSF pressure indicates minimal visual impairment.